Adolescent health problems in India: A review from 2001 to 2015 - Bej, Punyatoya (Indian Journal of Community Health, 2015)
Adolescence is a period in which all the habits and behaviour like high risk behaviour, substance abuse and eating habits develop that have lifelong impact. In India, programmes have been launched to address all the problems faced during adolescent period, still then adolescents are facing problems. In this review the problems faced by Indian adolescents were highlighted from the past 14 years’ studies. The studies were searched from 2001 to 2015 from Pub Med, Google scholar and other community medicine and public health related journals. The problems included were sexual health and teenage pregnancy, problems related to menstruation, illicit drugs, tobacco and alcohol use. Anaemia, eating problems, obesity, behavioural problems and oral health among adolescent were also reviewed. Nineteen abstracts and 52 full texts were available. Sexual health knowledge among adolescent varies from 41% to poor. Knowledge about sexually transmitted diseases and sexuality is less. Prevalence of dysmenorrhoea varies from 67.2% to 56.15% among adolescent girls. Prevalence of tobacco use varies from 25.1 to 12%. Prevalence of obesity varies from 3.4% to 0.35% and overweight varies from 5.5% to 5.84%. Prevalence of anaemia varies from 29% to 41.1%. Adolescents are facing depressive problems, physical fights, worry and loneliness. Prevalence of depression varies from 18.4% to 13.3%. Prevalence of dental problems varies from 18.2 to 41%. The review revealed that adolescents in India are facing problems of sexually transmitted infections, dysmenorrhea, tobacco and alcohol use, depression, physical fights, worry, loneliness and oral health problems. This needs a participation of family, community and government to resolve the issue.